Design and output characteristic analysis for power head of truck-mounted drilling rig. (June 2020) - Chang, Jianghua; Zhang, Yang; Tian, Honglinag; Lu, Feifei; Fan, Dong; Zhou, Zujie; Liu, Qingxiu
Abstract: Truck-mounted drilling rig is an important equipment for coalbed methane drilling construction, and the power head is one of the main actuators for truck-mounted drilling rig which has significant influence on technical feature of drilling rig. Now the power head of the rig is mostly driven by the motor + gear reduction unit to drive the main axle, the load change with the time, which had more influence on the rotation circuit. At the basis of analysis on load characteristics, a hydraulic control system with two-pump and two-circuit control was designed. The dynamic analysis model of the system is established, and the output characteristics of the system under no-load starting and on load starting are analysed. The analysis results show that: the response time of no-load starting pressure is 0.3s, the response time of on load starting pressure is 0.9s, the greater the load, the longer the response time; the output speed of the system reaches 120 r/min in the stable state.